Let’s simplify how to understand the chain rule for derivatives with an example.
Find the Outer and Inner Functions: For the function (f(x) = (3x + 5)^2), we can break it down like this:
Calculate the Derivatives:
Use the Chain Rule: The chain rule tells us that to find the derivative (f'(x)), we use this formula: [f'(x) = f'(u) \cdot u'] Now, let’s plug in the derivatives: [f'(x) = 2u \cdot 3 = 2(3x + 5) \cdot 3.]
Simplify the Expression: If we simplify it, we get: [f'(x) = 6(3x + 5).]
And that’s all there is to it! Just remember: you multiply the outer function’s derivative by the inner function’s derivative!
Let’s simplify how to understand the chain rule for derivatives with an example.
Find the Outer and Inner Functions: For the function (f(x) = (3x + 5)^2), we can break it down like this:
Calculate the Derivatives:
Use the Chain Rule: The chain rule tells us that to find the derivative (f'(x)), we use this formula: [f'(x) = f'(u) \cdot u'] Now, let’s plug in the derivatives: [f'(x) = 2u \cdot 3 = 2(3x + 5) \cdot 3.]
Simplify the Expression: If we simplify it, we get: [f'(x) = 6(3x + 5).]
And that’s all there is to it! Just remember: you multiply the outer function’s derivative by the inner function’s derivative!